0804 Sleep Bruxism, Awake Bruxism and Sleep Related Breathing Disorders in Adults With Down Syndrome. (27th May 2020) - Giannasi, L; Meira e Cruz, M; Rezende, T; Dutra, M; Nacif, S; Oliveira, E; Oliveira, L; Oliveira, W; Rode, S; Nazário, L; Silvestre, P; Bacigalupo, E; et al.
Abstract: Introduction: To our knowledge, no studies have accessed theawake bruxism (AB) and stage by stage sleep bruxism (SB) in adults with Down syndrome. Recent works have shown that portable PSG systems are accurate for SB assessment even in the absence of audio-video recording. We aimed to evaluate the prevalence of awake bruxism, stage-by-stage sleep bruxism and Sleep Related Breathing Disorders (SRBD) in adults with Down syndrome. Methods: Twenty-three adults with Down Syndrome (DS) were enrolled in this study. General health, dental status, parafunctional habits and temporomandibular symptoms were assessed. The history of SB/AB was taken from a questionnaire to the caregivers. A portable PSG type II system (Embla Embletta MPR+PG ST+Proxy, Natus, California-USA) was used to perform a full-sleep study at patients' home. RMMA activity was defined as low (>1 and <2 episodes/h of sleep), moderate (>2 and <4 episodes/h of sleep), or high (>4 episodes/h of sleep). PSG diagnose of SB was assumed if RMMA index was >2 episodes/h of sleep. Results: According to caregiver's report, AB was present in all patients whereas only 13.1% had SB. PSG records showed a SB prevalence of 91.3%, with a mean RMMA index 40.0±30.0/h. Only 2 (8, 7%) showed RMMA index of 0.0/h. SB episodes were predominant in N3 and REM sleep stage in 14 and 9 patients, respectively. All but one (95, 7%) patient (isolated snoring) presented with OSA (AHI=32.8±28.6). A unique TMD symptom (pain on palpation) was present in 8, 7% of the global sample. Conclusion: The high prevalence of "definitive SB" together with the high prevalence of OSA and snoring point in favor to the recommendation of routine PSG in adults with DS. Furthermore, the low sensitivity of parent-oriented questionnaires reinforces the need of more accurate assessment tools in order to get a better standard of care in this particular group of patients. Support: State of Sao Paulo Research Support Foundation - FAPESP grant number: 2017/06835-8